Strategi Pengembangan Literasi Menulis Siswa SMP melalui Pendekatan Multiliterasi pada Kegiatan Antologi Cerpen - Faridah Faridah; Eva Dianawati Wasliman; Sri Handayani (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
The evolution of literacy concepts toward multiliteracies demands transformation of writing instruction in junior high schools; however, its implementation has not been systematically integrated with instructional management. This study aims to describe and analyze strategies for developing junior high school students' writing literacy through a multiliteracy approach in short story anthology writing activities, examined through the functions of planning, organizing, implementing, and evaluating instruction. The research employed a qualitative approach with a case study design at SMPIT Al Fitrah Bandung. Data were collected through classroom observations, semi-structured interviews with teachers and the school principal, and documentation studies of instructional materials and student work. Data analysis utilized the Miles, Huberman, and Saldaña model, comprising data reduction, data display, and conclusion drawing and verification. Findings reveal that multiliteracy strategies were implemented through pre-writing, writing, and post-writing stages by integrating various literacy modes (textual, visual, digital). Implementation of strategies managed through instructional management functions effectively improved writing quality, particularly in idea development, plot construction, accuracy of intrinsic elements, creativity, motivation, and students' confidence. This study confirms that integrating the multiliteracy approach with instructional management effectively enhances junior high school students' writing literacy and provides theoretical and practical contributions to Indonesian language instruction developmentABSTRAKPerkembangan konsep literasi menuju multiliterasi menuntut transformasi pembelajaran menulis di sekolah menengah pertama, namun implementasinya belum terintegrasi dengan pengelolaan pembelajaran yang sistematis. Penelitian ini bertujuan mendeskripsikan dan menganalisis strategi pengembangan literasi menulis siswa SMP melalui pendekatan multiliterasi pada kegiatan penulisan antologi cerpen, yang ditinjau dari fungsi perencanaan, pengorganisasian, pelaksanaan, dan evaluasi pembelajaran. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus di SMPIT Al Fitrah Bandung. Data dikumpulkan melalui observasi pembelajaran, wawancara semi-terstruktur dengan guru dan kepala sekolah, serta studi dokumentasi terhadap perangkat pembelajaran dan karya siswa. Analisis data menggunakan model Miles, Huberman, dan Saldaña yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan dan verifikasi. Hasil penelitian menunjukkan bahwa strategi multiliterasi diterapkan melalui tahapan pramenulis, menulis, dan pascamenulis dengan mengintegrasikan berbagai moda literasi (teks, visual, digital). Penerapan strategi yang dikelola berdasarkan fungsi manajemen pembelajaran terbukti meningkatkan kualitas tulisan, terutama pengembangan ide, alur, ketepatan unsur intrinsik, kreativitas, motivasi, dan kepercayaan diri siswa. Penelitian ini menegaskan bahwa integrasi pendekatan multiliterasi dengan manajemen pembelajaran efektif meningkatkan literasi menulis siswa SMP dan memberikan kontribusi teoretis serta praktis bagi pengembangan pembelajaran Bahasa Indonesia.